Kisah sebagai Metode Pendidikan Akhlak dalam Perspektif Al-Qur`an - Mucharomah, Miftah (Edukasia Islamika : Jurnal Pendidikan Islam, 2017)
Akhlak constitutes the soul of Muslims so that it requires appropriate methods to build and enhance. The Qur’an signals that stories play pivotal roles in building and enhancing akhlak. It indicates that the stories need to be analyzed and documented so as to be transformed in human life, particularly in educational settings. This present study is aimed at investigating the roles of stories as a method of building and enhancing akhlak in the Qur’an perspectives. The collected data taken through library research method. The findings reveal that the stories in the Qur’an contribute very significant roles in building and enhancing akhlak. Additionally, building akhlak needs methods that are able to provide stimuli to human soul. It shows that the stories may lead to the dynamics of soul for encouraging humans to enhance their behavior. The stories in the Qur’an, likewise, possess several excellence. In addition to the high value of letters, the broad substance as well as the psychological aspect are included into the excellence of stories and are not owned by other methods, especially in accordance with the purity of human souls.